Approach Strategies for Family Conflicts in the Digital Age of the 21st Century (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2025)
This article aims to analyze the effectiveness of psychosocial intervention strategies for the resolution of family conflicts in the contemporary digital context. From this perspective, it is crucial to strengthen family ties in this new era, it is proposed to empower 21st century families so that they can live together in a healthy and harmonious way in the digital world, equipping families with the necessary tools to prevent and solve conflicts derived from the use of technology, promoting a positive relationship between the family and digital devices. Emphasizing the importance of creating homes where technology is an ally to strengthen family ties and not a source of division. Likewise, it seeks to promote open communication and respect for differences within diverse families, to build healthy and happy digital environments. At its core, it is about guiding families so that they can confidently and safely navigate the digital world, using technology responsibly and constructively to strengthen family ties.
Keywords: Family conflicts; digital era; intervention strategies; family communication; family dynamics; social intervention